Perkembangan Pendidikan Pada Zaman Penjajahan 1 (16-19) - Kusmawati , Heny; Mardliyya, Siti Rodliatam; Harumain, Ahmad (PT Literasi Nusantara Publisher, 2023)
This article deals with the history of Indonesian forms of education during the Dutch as well as Portuguese periods, particularly between the 16th and 19th centuries. The purpose of this article is to provide information about the background of education in Indonesia and the Indonesian education system, especially in the 16th to 19th centuries. To describe. This study uses historical techniques including the historical method used in this article, which includes several steps including criticism, heuristics, historiography and interpretation. The results of the study obtained show that the relations between Indonesian and European communities have developed over time, which has broad implications in several fields, for example in the field of education. In 1536, the Portuguese ruler Antonio Galvano established an education system in the form of a school for the first time in Indonesia, namely in Maluku. After the end of Portuguese rule, a new government was formed called the Dutch government. In which the Dutch formed a trading partnership system which is often known as the VOC.